2013
DOI: 10.3390/molecules180910132
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 (COX-2) Inhibition Constrains Indoleamine 2,3-Dioxygenase 1 (IDO1) Activity in Acute Myeloid Leukaemia Cells

Abstract: Indoleamine 2,3-dioxygenase 1 (IDO1) metabolizes L-tryptophan to kynurenines (KYN), inducing T-cell suppression either directly or by altering antigen-presenting-cell function. Cyclooxygenase (COX)-2, the rate-limiting enzyme in the synthesis of prostaglandins, is over-expressed by several tumours. We aimed at determining whether COX-2 inhibitors down-regulate the IFN--induced expression of IDO1 in acute myeloid leukaemia (AML) cells. IFN-γ at 100 ng/mL up-regulated COX-2 and IDO1 in HL-60 AML cells, both at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…Further studies have also shown COX2 inhibitors to augment a MUC1-based vaccine in a transgenic pancreatic cancer model in a manner that depended on suppressed IDO activity within tumor tissues ( 40 ). Similar roles for COX2 in promoting Tregs in non-small cell lung cancer and in elevating IDO expression in acute myeloid leukemia have also been described ( 41 , 42 ). Together, these studies suggest that COX2 represents an important regulator of IDO function within malignant tissues (Figure 2 B).…”
Section: Tumor-mediated Regulation Of Intrinsic Ido1 Expressionsupporting
confidence: 58%
“…Further studies have also shown COX2 inhibitors to augment a MUC1-based vaccine in a transgenic pancreatic cancer model in a manner that depended on suppressed IDO activity within tumor tissues ( 40 ). Similar roles for COX2 in promoting Tregs in non-small cell lung cancer and in elevating IDO expression in acute myeloid leukemia have also been described ( 41 , 42 ). Together, these studies suggest that COX2 represents an important regulator of IDO function within malignant tissues (Figure 2 B).…”
Section: Tumor-mediated Regulation Of Intrinsic Ido1 Expressionsupporting
confidence: 58%
“…We reasoned that IFN-γ may be the primary cytokine stimulus driving in vivo IDO expression in childhood AML, in analogy with other normal and tumor cell types [26] and also based on previously published data with human AML cell lines [27]. Also, it is conceivable that IDO − AML blasts may start expressing IDO when exposed to an IFN-γ-rich inflammatory milieu , implying that in vivo immune resistance mechanisms centered on IDO could be the result of AML blast cell interactions with IFN-γ-producing cell types, such as T cells or NK cells.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with AML at diagnosis have been reported to harbor dysfunctional T and NK cells, partly as a result of the tumor itself [29, 30]. In addition, AML-derived DC, AML cell lines and primary blasts from adults with AML may all express IDO1, either constitutively or after in vitro challenge with IFN-γ [27, 31, 32]. IDO mRNA has been detected in 52% of adults with AML in two different patient series [31, 33].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, enhanced iNOS staining was found in ACF transitioning from hyperplasia to dysplasia 78 . Several studies have shown that iNOS can up-regulate COX-2 expression 123127 and COX-2 has been shown to upregulate IDO1 expression in some cases 128130 . Clarifying the relationship between the complementary pathways may lead to the identification of novel and synergistic was to target CRC.…”
Section: Colon Cancer Relevant Pathways That Intersect With Ido1mentioning
confidence: 99%